Flexible meta-patch rectenna array for energizing low-power wearable medical sensors - Ahmad, Mohd Yazed; Alkhalaf, Hussein Yahya; Ramiah, Harikrishnan; Hossain, A K M Zakir; Azam, S M Kayser; Thiha, Aung (Institute of Electrical and Electronics Engineers Inc., 2024)
This article presents a low-cost 2× 2 metasurface-based rectenna array operating at the 2.45 GHz industrial, scientific, and medical (ISM) band, designed to power low-power wearable medical sensors (WMS). The proposed antenna is a novel textile-based metasurface interlayer patch (meta-patch) antenna fabricated on a felt fabric substrate, which replaces the conventional ground plane with a grounded metasurface consisting of a 3× 3 unit cell array. A single excitation port is used for both the patch antenna and the metasurface to improve gain, efficiency, and bandwidth. The meta-patch antenna achieved a high gain of 7 dB, an efficiency of 77%, and an enhanced bandwidth of 120 MHz. The rectifier employs a seven-stage Cockcroft-Walton Voltage Multiplier (CWVM) topology, fabricated on a rigid substrate. To evaluate the performance of the meta-patch rectenna array and the effect of adding more elements, the proposed meta-patch rectenna was tested in single-element, 2× 1 array, and 2× 2 array configurations under continuous RF power. The single-element, 2× 1 rectenna array, and 2× 2 rectenna array achieved power conversion efficiencies (PCE) of 52%, 53%, and 56%, with DC output powers of 414μ W, 429μ W, and 450μ W, respectively, at an input power of -1 dBm. The results demonstrate the potential of the proposed rectenna arrays for efficiently energizing low-power WMS.